Is the moral character of an artist relevant in the aesthetic evaluation of their work? - Aitken, Amelia (My University, 2022)
In light of the recent revelations of sexual predation in the artistic world, I seek to answer the question of whether it is morally plausible to include the moral character of the artist in our aesthetic evaluation of their work. In order to answer this question I consider the debate between aestheticism, which holds that art should be evaluated based on the formal aspects of the art only, and theories that hold that there should be some form of ethical component involved in the evaluation of art. Since these theories do not address the question of an artist’s moral character sufficiently, I argue that feminist aesthetics provide a suitable alternative to find a new framework in which to aesthetically evaluate art created by artists who make us uncomfortable without discarding their important contributions. Since this debate includes ethical considerations I turn to Kant’s deontological ethics to provide guidelines on what constitutes moral behaviour. In particular I consider the formula of the kingdom of ends to emphasise the importance of reciprocal responsibility in society.
A research report submitted in partial fulfilment of the requirements for the degree Master of Arts in Philosophy to the Faculty of Humanities, School of Social Sciences, University of the Witwatersrand, 2022